2012
DOI: 10.4103/1755-6783.98624
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of hydatid disease in rural central India: An 11-year experience

Abstract: Background: Hydatid disease or Echinococcosis is a zoonotic disease caused by the larva of Echinococcus species and is one of the oldest known diseases to man. The disease has a worldwide distribution and is also well recognized and documented in India. Aims: This study was carried out with the aim of describing the epidemiology (demography, clinical presentation, imaging characteristics, and in-hospital course) of Cystic Echinococcosis (CE) in central India. Materials and Methods: The clinical study of hydati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 17 publications
1
35
1
Order By: Relevance
“…Stray dogs are common in the region, resulting in widespread contamination with feces from potentially infected free-roaming dogs. Transmission may then result via contact with contaminated plants or soil followed by direct hand-to-mouth transfer [19]. Contaminated water may also play a role in parasite transmission; over three-quarters of the patients in the current study reported getting their water from a well rather than from a piped supply.…”
Section: Discussionmentioning
confidence: 81%
“…Stray dogs are common in the region, resulting in widespread contamination with feces from potentially infected free-roaming dogs. Transmission may then result via contact with contaminated plants or soil followed by direct hand-to-mouth transfer [19]. Contaminated water may also play a role in parasite transmission; over three-quarters of the patients in the current study reported getting their water from a well rather than from a piped supply.…”
Section: Discussionmentioning
confidence: 81%
“…[2] Liver and lung are the commonest sites affected, as they act as first and second filters respectively. G2 genotype (Tasmanian sheep strain) in buffalo has been reported from India.…”
Section: Discussionmentioning
confidence: 99%
“…While some reports from other countries like Turkey, Iran and India showed relatively similar peak age, the incidence was higher in females than males [6,[13][14][15][16]. Rao et al, have postulated that women are involved more than men in farming and herding livestock in their country; therefore women have more risk to get the disease [16]. The HD of human follows a relatively slow course.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed also multiple organ involvement in 26% of patients and the combination of liver and lung involvement was the highest (n=3; 16%). In some published reports, multiple organ involvement was ranged from 7.1% to 12% [4,7,16], and combined liver and lung HD were in 10.0% [18], and 19.3% [19] of patients.…”
Section: Discussionmentioning
confidence: 99%